2005
DOI: 10.1177/009164710503300102
|View full text |Cite
|
Sign up to set email alerts
|

Being a Good Neighbor: Can Students Come to Value Homosexual Persons?

Abstract: Attitudes toward gay/lesbian persons and behavior were initially assessed among Christian college students. Students with either uniformly positive or negative attitudes toward homosexual persons and behavior were then exposed to psychological and spiritual interventions designed to help them see more clearly the value of homosexual persons. Attitudes toward homosexual persons and behavior were then reassessed immediately after the intervention and one month later. Generally, the intervention improved attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Several studies have examined attitudes of undergraduate students from Evangelical colleges and universities. Results indicate that Evangelical students make a distinction between sexually active gays and lesbians and celibate ones (i.e., a person-behavior distinction; Bassett et al, 2005;Rosik et al, 2007), suggesting increased tolerance for persons with a same-sex attraction, as opposed to those who identify as gay, lesbian, or bisexual. This is often framed in Christian language as "loving the sinner, hating the sin."…”
Section: Current Studymentioning
confidence: 95%
“…Several studies have examined attitudes of undergraduate students from Evangelical colleges and universities. Results indicate that Evangelical students make a distinction between sexually active gays and lesbians and celibate ones (i.e., a person-behavior distinction; Bassett et al, 2005;Rosik et al, 2007), suggesting increased tolerance for persons with a same-sex attraction, as opposed to those who identify as gay, lesbian, or bisexual. This is often framed in Christian language as "loving the sinner, hating the sin."…”
Section: Current Studymentioning
confidence: 95%
“…Unfortunately, many of the older and more recent studies suffer from a number of methodological weaknesses, such as lack of a control or comparison condition (e.g., Bassett et al., ; Chng & Moore, ; Finkel, Storaasli, Bandele, & Schaefer, ; Green, Dixon, & Gold‐Neil, ; Nelson & Krieger, ; Penor Ceglian & Lyons, ; Van de Ven, ), small sample size (e.g., Bassett et al., ; Guth, Lopez, Rojas, Clements, & Tyler, ; Lance, ; Pagtolun‐An & Clair, ), limited follow‐up, if any (e.g., Cotton‐Huston & Waite, ; Finkel et al., ; Penor Ceglian & Lyons, ; Lance, ; Rye & Meaney, ), or nonrandom assignment to condition (e.g., Finken, ; Lance, ; Pettijohn & Walzer, ; Rye & Meaney, ; Serdahely & Ziemba, ; Stevenson & Gajarsky, ).…”
Section: Interventions To Reduce Sexual Stigma and Prejudicementioning
confidence: 99%
“…Other studies have suggested that homonegative beliefs and tolerance can coexist in religious persons and that for some conservative Christians there is no more inclination to avoid sexually active gay men than there is to avoid any other person displaying behavior believed to be immoral such as racism or drunkenness (Fulton, Gorsuch, & Maynard, 1999). Some research has also reported that strongly identified Christians have more positive attitudes and behavior toward celibate gay men than they do towards sexually active gay men (Bassett et al, 2000, 2001, 2005; Wilkinson & Roys, 2005).…”
Section: Discussionmentioning
confidence: 99%